Evaluation of the partially premixed compression ignition combustion with diesel and biodiesel blended diesel at part load condition - Tolgahan Kaya; Osman Akin Kutlar; Ozgur Oguz Taskiran (Engineering Science and Technology, an International Journal, 2021)
In this paper, alternative advanced combustion methods were investigated by conducting experiments at common operation condition (2000 rpm, 6.6 mg fuelling) of EURO-5 capable 1.5-liter diesel engine under NEDC. Single and double injection configurations of 6.6 mg at 2000 rpm were studied by adjusting SOI and EGR with pure diesel and biodiesel blended diesel. Power, NOx, Opacity, Start of Combustion and combustion data of the studied points were compared with the original condition of the 1.5 L diesel engine of the Ford Fiesta. Adjusting SOI and EGR for double injection configuration allowed reducing NOx emission from 65 ppm to 29 ppm and Opacity emission 1.2% to 0.2%. Utilization of biodiesel at single injection configuration reduced power almost 4% compared to pure diesel. More than 15% increase was observed for NOx emission, while opacity emission reduced 20% with biodiesel blended diesel compared to pure diesel. Although addition of biodiesel worsen the power, proposed advanced combustion method with pure diesel improve opacity, NOx and power compared to original condition of the engine.